Neighborhood Exposure to Violence and Delinquency in the Kingdom of Saudi Arabia: A Partial Test of Social Structure and Social Learning Theory - Connolly, Eric J. (Journal of interpersonal violence, 2021)
The social structure and social learning (SSSL) model for crime and deviance has received an impressive amount of empirical support in the United States and other Western industrialized countries. Comparatively, less research, however, has examined whether the SSSL model offers a viable framework for explaining variation in delinquent behavior in other geographic contexts, particularly, countries that place a stronger emphasis on social control stemming from both formal and religious sources. The current study addresses this void in the literature by examining a sample of youth from Saudi Arabia, a Middle Eastern country that enforces Sharia (a set of laws based in Islamic tradition) and strict gender roles. The association between neighborhood exposure to violence and risk for violent and nonviolent delinquent behavior was examined using structural equation models. Subsequent models were aimed at more closely examining the mediating role of delinquent peer association between neighborhood exposure to violence and violent and nonviolent delinquent behavior. Results indicate that males exposed to neighborhood violence are more likely to engage in violent and nonviolent delinquent behavior, whereas females are more likely to engage in violent, but not nonviolent, delinquent behavior. In line with the SSSL model, delinquent peer association fully mediates the direct effect of neighborhood exposure to violence on delinquent behavior in both males and females. Findings from the current study suggest that the SSSL model may provide a useful framework for explaining individual differences in delinquent behavior in Saudi Arabia.